Comprehensive genetic diversity and genome-wide association studies revealed the genetic basis of avocado fruit quality traits - Li, Jin; Eltaher, Shamseldeen; Freeman, Barbie; Singh, Sukhwinder; Ali, Gul Shad (Frontiers in Plant Science, 2024)
Introduction Avocado (Persea americana) is a highly nutritious fruit gaining worldwide popularity. However, its cultivation is currently reliant on a limited number of cultivars with restricted genetic diversity. This study aims to investigate the genetic diversity and population structure of avocado germplasm and identify genetic loci associated with key fruit quality traits that influence customer preference. Methods A diversity panel of 110 avocado accessions was analyzed using 4,706 high-quality single nucleotide polymorphisms (SNPs). Genetic diversity and population structure were analyzed using pairwise FST, AMOVA, admixture analysis, and phylogenetic analysis. Genome-wide association studies (GWAS) were conducted targeting nine fruit quality traits using two models: General Linear Model (GLM) with Principal Component Analysis (PCA) and Mixed Linear Model (MLM) with PCA and kinship (PCA + K). Results The analysis revealed three distinct populations corresponding to the three avocado ecotypes: Guatemalan, West Indian, and Mexican. Phylogenetic analysis indicated a closer relationship between the Guatemalan and West Indian races compared to the Mexican race in our Florida germplasm collection. GWAS led to identification of 12 markers within 11 genomic regions significantly associated with fruit quality traits such as fruit color, shape, taste, and skin texture. These markers explained between 14.84% to 43.96% of the phenotypic variance, with an average of 24.63%. Annotation of these genomic regions unveiled candidate genes potentially responsible for controlling these traits. Discussion The findings enhance our understanding of genetic diversity and population structure in avocado germplasm. The identified genetic loci provide valuable insights into the genetic basis of fruit quality traits, aiding breeding programs in developing improved avocado cultivars. Marker-assisted selection can accelerate the development of new varieties, promoting a more diverse and resilient avocado market.